ANALISIS PERAN IPAS DALAM MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS SISWA SD DI SDN BERTINGKAT NAIKOTEN 1 - Margareta E. Hurek; Trenchy A.M. Djami Balu (STKIP Subang, 2026)
This study aims to analyze how the role of science and natural sciences learning in developing critical thinking skills of students at SDN Bertingkat Naikoten 1. The focus of this study is to analyze the role of science and natural sciences learning in developing critical thinking skills of fifth grade students at SDN Bertingkat Naikoten 1. The Independent Curriculum emphasizes the importance of mastering critical thinking skills as an essential competency that must be possessed by 21st century students, by integrating science and social concepts considered relevant as a vehicle for developing these abilities. Science and natural sciences learning plays an important role in developing critical thinking skills of elementary school students through observation, exploration, and problem-solving activities that encourage students to analyze information, make the right decisions, and understand cause and effect relationships and everyday phenomena. The subjects of this study involved homeroom teachers VA and six students of class VA. The method used in this study is a qualitative descriptive method with data collection techniques through classroom observation and in-depth interviews. The results of this study indicate that science and natural sciences function as an effective driving factor in stimulating students' high-level cognitive abilities, especially in the aspect of critical thinking.